Research activity of the department of rhetoric and methods of teaching language and literature as a factor of improving the quality of university education - Proskalovich, Olga V.; Akushevich, Andrei A.; Sanikovich, Irina M.; Tayanovskaya, Irina V. (Journal of the Belarusian State University. Philology, 2024)
This article discusses the quality of research activities of the department of rhetoric and methods of teaching language and literature of the faculty of philology of the Belarusian State University. The vision of the goal, general objectives, directions and prospects for the scientific and innovative activities of the department is outlined. The role of the department in ensuring high level of university education is emphasised.